Nanotechnology in the Laboratory: Applications and Future Prospects - Alwethaynani Mohammed Salem,; Ali Abdullah Mohammed Alkhathami,; Yasser Suliman Alhelio,; Hanaa Abdullah Alyamani,; Sahar Mohammed Aljaddawi,; Raed Musaad Nafi' Al-Harbi,; ‏Mohammed Abdullah Abdulrhman Alamri,; Yousef Omar Alahmadi,; Abdulraouf Ahmed Mohammed Saleh,; Hassan Mohammed Alshareef,; Ziyad Saleh Alluqmani, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The integration of nanotechnology into laboratory practices has been transformative, offering innovative solutions across various scientific disciplines. This study explores the burgeoning field of nanotechnology within laboratory settings, emphasizing both current applications and future prospects. Leveraging secondary data from a wide array of scientific publications, industry reports, and academic research, the study provides a comprehensive analysis of how nanotechnology is revolutionizing laboratory methodologies and outcomes. Key applications identified include precision drug delivery systems, nanoscale diagnostic tools, and advanced materials for laboratory equipment that enhance performance and efficiency. The study also addresses challenges such as scalability, ethical considerations, and potential environmental impacts. Future prospects for nanotechnology suggest significant advancements in personalized medicine, improved diagnostic techniques, and the development of sustainable materials. By synthesizing existing data, this study aims to provide a clear understanding of the current landscape of nanotechnology in laboratories and inspire further research and innovation in this transformative field.